2004
DOI: 10.1590/s0101-81752004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Estimativa do tamanho de duas espécies de ciclídeos (Osteichthyes, Perciformes) predados por Lontra longicaudis (Olfers) (Carnivora, Mustelidae), através de análise das escamas

Abstract: O presente estudo foi realizado no Vale do Taquari, região central do Estado do Rio Grande do Sul, sul do Brasil. Entre dezembro de 2001 e dezembro de 2002 foi realizado um estudo sobre a predação de Cichlidae por Lontra longicaudis (Olfers, 1818) através de análise das escamas encontradas nas fezes de lontra. Foi identificada a predação sobre Gimnogeophagus labiatus (Hensel, 1870) e Crenicichla punctata Hensel, 1870, e a ocorrência destas espécies de peixe na dieta é mais elevada do que sua disponibilidade re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 2 publications
0
5
1
3
Order By: Relevance
“…There are very few references about the size of prey taken by the Neotropical otter (QUADROS & MONTEIRO-FILHO, 2001;KASPER et al, 2004b). However, it is probable that the species does not dedicate much time attempting to capture large-sized prey.…”
mentioning
confidence: 99%
“…There are very few references about the size of prey taken by the Neotropical otter (QUADROS & MONTEIRO-FILHO, 2001;KASPER et al, 2004b). However, it is probable that the species does not dedicate much time attempting to capture large-sized prey.…”
mentioning
confidence: 99%
“…A list of potential prey species for otters was made, consisting of all the fish species reported in the study area that have a reported maximum total length ≥ 100 mm (S1 Table). Size selection was based on the assumption that otters prefer to feed on fish within the 100-150 mm size range [53]. Prey remains that could be identified were fish scales, otoliths or vertebra; crustacean shells; and mammal hairs.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is probable that environmental fluctuations, prey availability, prey microhabitat, conspicuousness, and palatability could be some factors that influences the prey selection and not only differences in dentition in the otters species or escape ability and size of prey (Pardini 1998, Kasper et al 2004b, Perini et al 2009 …”
Section: Seasonal Prey's Fluctuationsmentioning
confidence: 99%